Corrosion and thermal stability of multi-walled carbon nanotubeegraphiteeacrylonitrileebutadieneestyrenecomposite bipolar plates for polymer electrolyte membrane fuel cells - Lopes De Oliveira, M.C.; Ett, G.; Altobelli Antunes, R.
synthetic graphite particles and acrylonitrileebutadieneestyrene (ABS)powder have been produced by hot compression molding. The corrosion properties of the molded plates were assessed through electrochemical impedance spectroscopy (EIS)and potentiodynamic polarization curves. Through-plane and in-plane electrical conductivities were determined. The relevance of electrochemical oxidation to the electrical conductivity of the composites was assessed by cyclic voltammetry. Thermal stability of the composites was examined by thermogravimetric analysis (TGA). The morphology of fractured surfaces of the plates was observed by scanning electron microscopy. The incorporation of MWNTs increased the inplane and through-plane electrical conductivity of the ABSegraphite composites. There was, though, a corresponding reduction of the corrosion resistance. The thermal behavior was little affected by the addition of MWNTs
Keywords: COMPOSITE BIPOLAR PLATES; PEM FUEL CELLS; MULTI-WALLED CARBON NANOTUBES; ACRYLONITRILEEBUTADIENEESTYRENE; CORROSION; TGA